2020
DOI: 10.1016/j.heliyon.2020.e03784
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of magnetite/silica nanocomposites from natural sand to create a drug delivery vehicle

Abstract: In this study, we report the synthesis of the magnetite/silica nanocomposites and their structural and functional groups, magnetic properties, morphology, antimicrobial activity, and drug delivery performance. The X-ray diffraction characterization showed that magnetite formed a spinel phase and that silica formed an amorphous phase. The particle sizes of magnetite increased from 8.2 to 13.2 nm with increasing silica content, and the particles were observed to be superparamagnetic. The nanocomposites tended to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 62 publications
1
23
0
Order By: Relevance
“…The magnetic properties of Fe 3 O 4 /PPY/CNT nanocomposite were studied using vibrating-sample magnetometer. where the magnetization of magnetite decreased from 30 to 9 emu/gr after the incorporation of silica [17]. Furthermore, due to the small coercivity value, Fe 3 O 4 /PPY/CNTs can be classified as a soft magnet material group.…”
Section: Resultsmentioning
confidence: 99%
“…The magnetic properties of Fe 3 O 4 /PPY/CNT nanocomposite were studied using vibrating-sample magnetometer. where the magnetization of magnetite decreased from 30 to 9 emu/gr after the incorporation of silica [17]. Furthermore, due to the small coercivity value, Fe 3 O 4 /PPY/CNTs can be classified as a soft magnet material group.…”
Section: Resultsmentioning
confidence: 99%
“…The other materials were TMAH used as the surfactant, H 2 O used as the carrier liquid, HCl (38%) used as the solvent, and NH 4 OH (25%) used as the precipitating agent. Dried natural iron sand was separated from impurities using a permanent magnet to produce Fe 3 O 4 powder with a purity of 99.5% [ 15 ]. Twenty grams of Fe 3 O 4 powder was reacted with 58 mL of HCl using a magnetic stirrer for 30 min at room temperature to obtain ferric chloride and ferrous chloride.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Therefore, in this study, we developed a fabrication method of Mn 1 -x Zn x Fe 2 O 4 ferrofluids using abundant natural iron sand as the main precursor that is effective, efficient, inexpensive, and ecofriendly. Natural iron sand can be employed effectively to minimize the fabrication cost for the synthesis of high quality magnetic nanoparticles [ 15 ]. Moreover, to further reduce the fabrication cost, water was used as the polar carrier liquid in the fabrication of Mn 1 -x Zn x Fe 2 O 4 ferrofluids with a chain-like structure.…”
Section: Introductionmentioning
confidence: 99%
“…The subtraction of wavenumber was also referred as the decrement of sand impurities concentration. Furthermore, the specific peak of the magnetite/silica bond as Fe-O-Si was detected at 565 cm -1 only on the sample A [14][15][16]. Significantly, the disappearance of Fe-O-Si on FTIR spectra of sample B indicated that there was no interaction between magnetite and silica.…”
Section: Analysis Of Tobacco Dust With Fourier Transform Infrared mentioning
confidence: 99%